Local Leadership Communications in the Tradition of Ngaruwat Bumi in the Traditional Village Of Banceuy, Subang District - Vera Hermawan; Ardianti, Dhini (Lembaga Penelitian Universitas Pasundan, 2023)
This research explains local leadership communication in the Ngaruwat Bumi tradition in Banceuy Village, Subang Regency. The description of the life of the Banceuy Village community as seen from local leadership based on social position and the social role of the actors in the Banceuy Traditional Village community is important in seeing the course of Ngaruwat Bumi rituals and traditions. This local leadership role is related to religion and belief which is centered on the Tatali Karuhun value system as a legacy of previous ancestral traditions. The myth of Dewi Sri, known as the spiritual figure Nyi Pohaci, was transformed into a rice plant, the staple food of the local community. So rice is considered a holy and sacred plant. This ritual is a way of honoring the existence of Dewi Sri (Goddess of Rice) who has given blessings to the lives of the people of Banceuy Traditional Village by dancing and singing Dewi Sri. The method used in this research is a qualitative method with a qualitative descriptive approach, through observation, literature study and interviews with traditional leaders of the Banceuy Indigenous village using purposive sampling techniques. The research results show that communication and the role of local leadership through the Ngaruwat Bumi ritual in Banceuy Subang Village is a local tradition that emphasizes the importance of ritual in fostering dialogue between humans and nature. This involves various aspects, including verbal, symbolic and social interactions, which aim to maintain and strengthen cultural identity and community values. These rituals also function as mediators of conflict between local residents and external authorities, increasing cultural awareness, environmental conservation, and social life.